24-hour blood pressure profile in children with chronic pyelonephritis and chronic kidney disease stages I–III - Vakulenko, L.I. (KIDNEYS, 2021)
Background. Blood pressure (BP) monitoring is important for the management of patients with chronic kidney disease (CKD), both for the conventional cardiovascular risk reduction and long-term preservation of kidney function. The purpose was to study the features of 24-hour blood pressure profile in children with chronic pyelonephritis (CPN) and CKD stages І–ІІІ. Materials and methods. A total of 94 patients aged from 6 to 17 years with chronic pyelonephritis in remission and CKD stages І–ІІІ were examined. 24-hour ambulatory blood pressure monitoring (ABPM) was carried out followed by mathematical processing. Results. Thus, a comparative analysis of the systolic (SBP) and diastolic blood pressure (DBP) indicators obtained within a single BP measurement and during 24-hour ABPM showed their differences in 25.5 % of cases. According to ABPM findings, 22.3 % of CKD children demonstrated elevated BP and 34.0 % — arterial hypertension (АН). It was found that the relative number of patients with sustained and labile AH gradually increased with a decrease in renal functions (mild-to-moderate CKD progression). The analysis of night-time BP dipping degree in patients with CKD revealed a gradual decrease in the relative number of patients with optimal BP dipping for both SBP (from 61.7 % in CKD stage I to 47.1 % in CKD stage III) and DBP (53.2 and 11.8 %, respectively; р = 0.0049). Night-peakers with night-time stable elevation of SBP (11.8 %) and DBP (29.4 %) were the patients with CKD stage III. Conclusions. The number of hypertensive patients increases among CPN children during CKD progression. AH in children with progressive nephropathy is characterized by a greater contribution from DBP and stable elevation of night-time BP.